Short Term Complications of Acute Myocardial Infarction in a Tertiary Hospital (Medicine Today, 2021)
Introduction: Acute myocardial infarction is very common in Bangladesh. It is one of the most common causes of mortality worldwide. The clinical course is associated with various complications.Materials and Methods: To assess the short-term outcome of acute coronary syndrome we select 100 patients. The study was conducted at the Medicine wards of Khulna Medical College Hospital, Khulna from February’2019 to August’2019. We observed the clinical presentations, ECG findings, echocardiographic findings, short term complications and outcome.Results: We found that most of the patients (61%) were within 45-64 years of age. Chest pain was the most common (85%) presentation. NSTEMI is more common than STEMI. 53% patients developed complications. Acute LVF is the most common (23%) complication. AV block is the most common arrythmia (10%). We found overall mortality 38%.Conclusion: Early detection of complications is essential for reduction of morbidity and mortality. This study will help to evaluate short-term complications and to give appropriate management.Medicine Today 2021 Vol.33(1): 42-44